Some Characterizations of Weighted Holomorphic Function Classes by Univalent Function Classes - A. El-Sayed Ahmed; S. Omran (Journal of Function Spaces)
Some characterizations of QK,ωp,q− type classes of holomorphic functions by Schwarzian derivatives with known conformal-type mappings are introduced in the present manuscript. Moreover, the action of the pre-Schwarzian derivatives on QK,ωp,q− type classes, typically the univalent ones by using concerned Carleson-type measures, is investigated. In addition, we reveal important characterizations of some concerned weighted analytic-type spaces with the known Schwarzian derivatives evolving certain Q−type of concerned function class for a high utility toward practical and feasible application of concerned domains.